Urgensi Pemahaman Politik Dan Hukum Dalam Menghadapi Dinamika Organisasi Pemuda Muhammadiyah Di Kota Medan - Muhammad Irsyad (Iuris Studia: Jurnal Kajian Hukum, 2020)
Muhammadiyah gives freedom to every member of the organization to exercise their rights in political life in accordance with all statements. The right to vote must be responsible as citizens who act rationally and decisively, in line with Muhammadiyah's mission and interests, in the interests of the nation and state. This writing uses normative juridical legal research methods (normative research). The nature of this research is descriptive, which aims to provide an overview of social symptoms concerning the role of psychiatrists in proving psychological violence in criminal acts of domestic violence. Sources of research data are primary legal materials, secondary legal materials and tertiary legal materials. The data collection method was carried out using document study techniques, which were analyzed using qualitative analysis techniques. Based on the results of research that the Muhammadiyah Youth according to these ideals Muhammadiyah organizations choose to fight in the life of the nation and state through efforts to develop or empower the people to achieve civil society (civil society) as strong as Muhammadiyah's goals to achieve Islamic society sincerely. Meanwhile matters related to state policy as a process and outcome of the political function of government will follow them through an appropriate and wise approach in accordance with the principles of effective interest group struggle in a democratic state life that truly gives priority to the interests of the people. and uphold the values of the school, such as those which became the spirit of the rules and the formation of the Republic of Indonesia in 1945